Hydrothermal carbonization of food waste as sustainable energy conversion path. (November 2022) - Son Le, Huu; Chen, Wei-Hsin; Forruque Ahmed, Shams; Said, Zafar; Rafa, Nazifa; Tuan Le, Anh; Ağbulut, Ümit; Veza, Ibham; Phuong Nguyen, Xuan; Quang Duong, Xuan; Huang, Zuohua; Hoang, Anh Tuan
Graphical abstract: Highlights: Hydrothermal carbonization is an attractive method to convert food waste to energy. Reaction mechanism in hydrothermal carbonization of food waste is scrutinized. Critical parameters and characteristics of hydrothermal carbonization are presented. Hydrothermal carbonization could manage efficiently up to 70% of food waste. Abstract: Every day, a large amount of food waste (FW) is released into the environment, causing financial loss and unpredictable consequences in the world, highlighting the urgency of finding a suitable approach to treating FW. As moisture content makes up 75% of the FW, hydrothermal carbonization (HTC) is a beneficial process for the treatment of FW since it does not require extensive drying. Moreover, the process is considered favorable for carbon sequestration to mitigate climate change in comparison with other processes because the majority of the carbon in FW is integrated into hydrochar. In this work, the reaction mechanism and factors affecting the HTC of FW are scrutinized. Moreover, the physicochemical properties of products after the HTC of FW are critically presented. In general, HTC of FW is considered a promising approach aiming to attain simultaneously-two core benefits on economy and energy in the sustainable development strategy.